Diseño de un sistema de gestión en la Contraloría General de la República para lograr la carbono neutralidad - Villalta-Rivera, Brayan José (Instituto Tecnológico de Costa Rica, 2017)
With the objective of designing an information management system to account for the possible carbon neutrality in the General Comptroller's Office of the Republic of Costa Rica. A GHG emissions inventory was prepared for 2016 as the base year under the official established methodology using the national standard INTE-ISO 14064-1. The evaluated direct emissions sources were fuels (garden equipment, vehicles and emergency plants), air conditioners (offices and vehicles) and nitrogen fertilizers; in addition to indirect emissions by electricity consumption. It was determined that the emission of greenhouse gases for the base year is 148.53 tCO2e; the activities that represent the highest amount of emissions come from electric power consumption with 54,33 tCO2e, diesel with 34.51 tCO2e and gasoline with 31.58 tCO2e from vehicles; which represents 37%, 23% and 21% respectively of the total GHG emissions inventory. As part of the management system necessary to account for C-neutrality, procedures and registers were developed for an adequate tally and to have adequate flow of information and thereby guarantee the availability and accuracy of the data. The proposed reduction measures are based on the results obtained from GHG emissions and from the improvement options detected in the different activities or emission sources. The reduction efforts made by the institution are focused on energy efficiency, travel and transport management and the substitution of the vehicle energy matrix. The proposed reduction measures aim to increase energy efficiency and provide a partial change of the institution's electricity matrix.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2017.
Keywords: Carbono neutral; Inventarios; Efecto invernadero; Gases; Gestión